Do Motivational Strategies Improve the Effects of a Small-Group Math Intervention Program?. Issue 3 (2nd July 2020) - Codding, Robin S.; Begeny, John; Kromminga, Kourtney R.; Edmunds, Rebecca R.; Klaft, Jenna; Diggs, Calvary; Hansen-Burke, Annie
Abstract: Overall mathematics proficiency of fourth graders in the U.S. continues to be poor and students falling at or below the 25 th percentile display declining performance (NCES, 2017), which suggests the need for schools to provide supplemental intervention supports as soon as skill gaps are observed. Unfortunately, there is a paucity of small group intervention programs that address whole number knowledge for elementary-aged children. Moreover, the contribution of motivational aspects of small group academic interventions is understudied and may be important for enhancing persistence and effort in mathematics. The purpose of this study was to examine the relative impact of two forms of intervention on mixed addition and subtraction fact fluency with second grade students: (a) evidence-based instructional components alone, and (b) a combination of instructional and motivational components. A multiple baseline design across three groups of second grade students was employed. Across groups, students benefitted from the combined intervention of both instructional and motivational components. Individual performance suggested variability in responsiveness to treatment. Participants rated the combined treatment package more favorably than the instructional components in isolation.